Policy of national physical education journals on review articles/systematic reviews Política de periódicos nacionais em educação física para estudos de revisão/sistemática - Schutz G.R.* (2011)
The large amount of scientific information that is produced and available in different areas, including physical education, requires the summary of contents. Different synthesis/review methods that lead to different answers are available. The objective of this study was to analyze the policy of national physical education journals on review articles, to quantify the reviews, and to classify them as systematic and narrative reviews based on established criteria. All journals (n=13) offer the possibility to publish review articles, but do not have specific standards/methods for this type of article. The production of review articles was high (n=429), with the publication of 371 (86%) narrative reviews and 58 (14%) systematic reviews. A priori, narrative reviews are used for the production of knowledge by internationally renowned scientific researchers. However, the volume of production of this type of review, as diverse as the issues in physical education are, does not seem to be proportional to the number of recognized researchers. This fact can lead to lower quality of the scientific production and rejection of these articles, as observed for journals in other areas. In view of the criteria and method employed, systematic reviews seem to be more valuable in situations in which no renowned researchers wants to produce review articles, avoiding a poor outcome. This type of review is characterized by more scientific rigor, whose production follows specific steps and standards, and also seems to be more appreciated by journal editors, with these reviews sometimes even being classified as original articles.